Vedolizumab in Inflammatory Bowel Disease Associated with Autoimmune Liver Disease Pre- and Postliver Transplantation: A Case Series. Issue 10 (October 2016) - Lim, Tiong Yeng; Pavlidis, Polychronis; Gulati, Shraddha; Pirani, Tasneem; Samaan, Mark; Chung-Faye, Guy; Dubois, Patrick; Irving, Peter; Heneghan, Michael; Hayee, Bu'Hussain
Abstract : Article first published online 25 August 2016.